GREEN FERROCHROME PRODUCTION FROM CHROMITE ORE BY HYDROGEN PLASMA SMELTING REDUCTION (HPSR) - Tandersen, Dale
Chromium is a crucial component in steel alloys, particularly for stainless steel, due to its ability to form a protective layer on the surface when exposed to air. Typically, chromium is produced in the form of ferrochrome, which is obtained through the carbothermic reduction and refining of chromite ore at high temperatures. The ferrochrome produced by this method is high-carbon ferrochrome, containing 6-9% carbon. This process results in CO2 emissions of 5.4 tons per ton of high-carbon ferrochrome. Carbon poses a problem for stainless steel production because it can cause intergranular corrosion by forming Cr23C6, which reduces the chromium content at grain boundaries and, consequently, reduces corrosion resistance. To address this issue, argon oxygen decarburization (AOD) and/or vacuum oxygen decarburization (VOD) processes are used. Hydrogen plasma smelting reduction (HPSR) could offer a solution to both emissions and carbon content issues in ferrochrome production. Using this process for ferrochrome production, we aim to produce carbon-free ferrochrome and more sustainable process for ferrochrome production. A series of chromite ore reduction experiments using HPSR were conducted to study the effect of SiO2 and CaO fluxes, the effect of SiO2 amount, and reduction duration on the produced ferrochrome. The experiments began with initial characterization of chromite ore using X-ray fluorescence and X-ray diffraction analysis. Calcined dolomite and calcined limestone were used as CaO sources and initially analyzed using X-ray fluorescence. The gas flow rate was set at 5 liters per minute with an H2/Ar ratio of 4/1. Flux variation experiments involved using briquettes made of 2 grams of chromite ore sample with 10 wt.% SiO2 or CaO, with a reduction duration of 60 seconds. SiO2 amount variation experiments used briquettes made of 2 grams of chromite ore sample and silica ranging from 0 wt.% to 20 wt.% with a reduction duration of 60 seconds. Reduction duration variation was studied using briquettes made of 1 gram of chromite ore with 20 wt.% SiO2 and reduction durations from 30 to 360 seconds. The results were analyzed using scanning electron microscopy – energy dispersive spectroscopy to determine the composition of the metal and slag produced. iv The use of SiO2 as a flux resulted in higher chromium content in the metal compared to CaO, as SiO2 aids the reduction process by aiding aluminium and magnesium ions exchange with chromium ions in the slag and also SiO2 helps to reduce slag melting temperature. Meanwhile CaO is generally used to reduce slag viscosity and melting point. Increasing the amount of SiO2 used resulted in higher chromium content in the metal. Using 20 wt.% SiO2, chromium content of 30.54% was achieved in the metal. Chromium content in the metal increased with longer reduction durations. Iron oxide was reduced first, with iron reduction completing in just 240 seconds, achieving 98% recovery, while chromium oxide reduction completed in 360 seconds with a 72% recovery. Ferrochrome with ±50% chromium content can be produced in just 240 seconds. Chromium oxide reduction finished after 360 seconds.